Investigating the Knowledge Surrounding Folate and Folic Acid in a Cohort of Vegetarians - Michael Dolan; Katherine Younger; Lucy Brennan; Jessica Roche (SURE Journal: (Science Undergraduate Research Experience Journal))
BackgroundThe aim is to identify any gaps in the knowledge of folate and folic acid in vegetarians, which is of interest given the increasing adoption of vegetarian type diets. MethodsIn this convenience sample, 106 people answered an online questionnaire regarding folate intake and awareness among vegetarians. This was created using Google Forms and was shared via Facebook, including on various national and college vegetarian group pages. There were 44 questions. Twenty-four participants were excluded, because they reported eating fish, chicken or other meat. Final data analysis included 82 subjects. The majority of these vegetarians were females over the age of 30. ResultsFifty-five percent of those aged23% of those >30, did not know the recommended stage for folic acid supplementation. Thirty-four percent of females, did not know any good food sources of folate compared to 67% of males. ConclusionsThere was an overall lack of knowledge regarding the recommended stage for folic acid intake and the required quantity of folic acid to be taken among vegetarians. This research suggests that more public health campaigns are needed in order to increase the knowledge and intake of folic acid.